Tellurium-copper alloy material and preparation method thereof
By forming a copper tellurium tellurium complex solution in the preparation of copper tellurium alloy, spray drying, calcining and reducing treatment, and doping rare earth raw materials, the problem of uneven element distribution is solved, and the performance and application potential of the material are significantly improved.
Patent Information
- Application Number
- CN202411848779.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-16
- Publication Date
- 2025-03-25
- Estimated Expiration
- 2044-12-16
AI Technical Summary
In the existing copper tellurium alloy preparation technology, uneven element distribution leads to degradation of material properties and the risk of cracking and brittle fracture during processing, limiting its potential in high-performance applications.
By forming a copper tellurium complex solution, spray drying, calcining and reducing treatment, and doping with rare earth raw materials, the tellurium copper tellurium alloy material is prepared by sintering.
It significantly improves the uniformity of the material and refines the grain structure, improves the conductive properties, tensile strength and high-temperature oxidation resistance of the alloy, and broadens its potential in industrial applications.
Smart Images

Figure CN119681273A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of tellurium-copper alloy preparation, and in particular to a tellurium-copper alloy material and a preparation method thereof. Background Art
[0002] As a copper alloy material with excellent performance, tellurium copper alloy occupies an important position in the industrial field due to its unique physical and chemical properties. This alloy is famous for its high electrical conductivity, high thermal conductivity, excellent corrosion resistance and good processing performance. Tellurium copper alloy has a wide range of applications, including electronics, electrical, automotive, aerospace and other industries, especially in electronic and electrical equipment as connectors and contact materials.
[0003] The existing tellurium copper alloy preparation technology mainly involves the steps of smelting, casting, heat treatment and deformation processing. In the smelting process, the copper ingot is first melted, and the oxygen in the raw material is removed by controlling the furnace temperature and adding a deoxidizer. Then the tellurium copper master alloy is added, and the smelted alloy is cast into ingots, and then subjected to extrusion deformation processing, rolling deformation processing and heat treatment processes, and finally the tellurium copper alloy material is obtained. Although these methods can produce tellurium copper alloys with certain properties, there are still some defects in practical applications.
[0004] First of all, the uniformity of the distribution of tellurium, nano-ceramic phase and rare earth elements in tellurium copper alloy is crucial to the overall performance of the material. The uniform distribution of these elements can improve the performance of the material through a variety of strengthening mechanisms, including solid solution strengthening, fine grain strengthening, second phase strengthening and purification of rare earth elements. However, when preparing tellurium copper alloy by smelting method, due to the difficulty in accurately controlling the physical and chemical conditions during the smelting process, there is often segregation of alloying elements during the solidification process, resulting in uneven distribution of elements, which is particularly obvious at the grain boundaries.
[0005] Secondly, when the distribution of alloying elements in the copper alloy matrix is uneven, a series of adverse consequences will occur. For example, the continuous distribution of brittle second phases on the grain boundaries and the significant segregation of microalloying elements will not only significantly reduce the electrical conductivity and mechanical strength of the material, but also greatly increase the risk of cracking and brittle fracture during processing. In addition, this uneven distribution will also weaken the strength performance and oxidation resistance of the material in high temperature environments, thereby adversely affecting the overall reliability of the material.
[0006] In summary, the main problems faced by the existing technology in the preparation of tellurium copper alloys include the uneven distribution of elements, the resulting degradation of material properties, and the risk of cracking and brittle fracture during processing. These problems limit the potential of tellurium copper alloys in high-performance applications, especially in fields with extremely high requirements for material properties. Therefore, achieving uniform distribution of elements in tellurium copper alloys is of great significance for improving material properties and expanding its application range.
[0007] In view of this, the present invention is proposed. Summary of the invention
[0008] The object of the present invention is to provide a tellurium-copper alloy material and a preparation method thereof. The preparation method significantly improves the high-temperature strength and electrical conductivity of the alloy by optimizing the preparation process of the alloy, thereby obtaining a high-quality tellurium-copper alloy material with high electrical conductivity, high thermal conductivity and high strength characteristics.
[0009] In order to achieve the above-mentioned purpose of the present invention, the following technical solutions are particularly adopted:
[0010] In a first aspect, the present invention provides a method for preparing a tellurium-copper alloy material, wherein the tellurium-copper alloy material is prepared by forming a tellurium-copper complex solution from a tellurium-copper raw material, subjecting the solution to a spray drying treatment, a calcination and a reduction treatment, and doping the solution with a rare earth raw material, followed by sintering.
[0011] In an optional embodiment, the method for preparing the tellurium copper alloy material comprises:
[0012] The copper telluride complex solution is prepared by using a metal chelating agent to prepare the metal salt and telluric acid in the copper telluride raw material;
[0013] spray drying the copper tellurium complex solution to obtain a precursor powder;
[0014] The precursor powder is subjected to calcination and reduction treatment to obtain an Al2O3-CuTe alloy composite;
[0015] Mixing the Al2O3-CuTe alloy composite with a rare earth raw material to obtain a rare earth mixture;
[0016] The rare earth mixture is sintered to obtain the tellurium copper alloy material.
[0017] Preferably, the metal salt is a metal salt that is soluble in water and has no residual elements other than the target element after thermal decomposition;
[0018] Preferably, the metal salt comprises a copper ion metal salt with copper as the target element;
[0019] Preferably, the metal salt further comprises an aluminum ion metal salt with aluminum as the target element;
[0020] Preferably, the copper ion metal salt includes copper nitrate and copper acetate;
[0021] Preferably, the aluminum ion metal salt includes aluminum nitrate and aluminum acetate;
[0022] Preferably, the tellurium-copper alloy material comprises 0.2-1.0 wt.% of tellurium, 0-0.5 wt.% of Al2O3, and 0-0.2 wt.% of the rare earth raw material.
[0023] In an optional embodiment, the process of preparing the copper tellurium complex solution by using a metal chelating agent to prepare the metal salt and telluric acid comprises:
[0024] Dissolving the metal salt and telluric acid in water and mixing them into a solution;
[0025] adding the metal chelating agent to the dissolving solution to form the tellurium copper complex solution containing the metal complex;
[0026] In an optional embodiment, the metal chelator contains a hydroxyl functional group that can form a complex with copper ions and aluminum ions; and the material structure of the metal chelator carries a negative charge that can attach to the surface of the metal complex particles;
[0027] In an alternative embodiment, the metal chelator comprises citric acid, ethylenediaminetetraacetic acid, nitrilotriacetic acid and diethylenetriaminepentaacetic acid.
[0028] In an optional embodiment, the step of spray drying the copper tellurium complex solution to obtain a precursor powder comprises:
[0029] atomizing the copper tellurium complex solution to form ultrafine droplets;
[0030] Drying the ultrafine droplets by hot air to obtain the precursor powder;
[0031] In an optional embodiment, the rotation speed of the atomization equipment for the atomization treatment is 4000rpm to 30000rpm;
[0032] In an optional embodiment, the ultrafine droplets are dried by hot air, and the temperature of the air inlet is 100°C to 300°C.
[0033] In an optional embodiment, the precursor powder is subjected to calcination and reduction treatment to obtain an Al2O3-CuTe alloy composite, comprising:
[0034] calcining the precursor powder in air or oxygen atmosphere to obtain a composite oxide;
[0035] Passing a reducing gas into the composite oxide for reduction treatment to obtain the Al2O3-CuTe alloy composite;
[0036] In an optional embodiment, the calcination time of the calcination treatment is 10 minutes to 180 minutes;
[0037] In an optional embodiment, the calcination temperature is 100°C to 600°C;
[0038] In an optional embodiment, the temperature of the reduction treatment is 200° C. to 800° C.;
[0039] In an optional embodiment, the reduction time of the reduction treatment is 10 minutes to 180 minutes;
[0040] In an optional embodiment, the reducing gas for the reduction treatment includes hydrogen, or a mixed gas consisting of hydrogen and at least one of nitrogen and argon.
[0041] In an optional embodiment, the purity of the rare earth raw material is not less than 99%; and / or the particles of the rare earth raw material are less than 10 μm; and / or the treatment time of mixing the Al2O3-CuTe alloy composite with the rare earth raw material is 1 hour to 72 hours.
[0042] In an optional embodiment, the rare earth mixture is sintered to obtain the tellurium copper alloy material, comprising:
[0043] Performing a molding process on the rare earth mixture to obtain a block;
[0044] sintering the block to obtain the tellurium-copper alloy material;
[0045] In an optional embodiment, the molding process includes any one of molding and cold isostatic pressing;
[0046] In an optional embodiment, the pressure of the molding process is 50MPa to 350MPa;
[0047] In an optional embodiment, the holding time of the molding process is 5 seconds to 300 seconds;
[0048] In an optional embodiment, the sintering atmosphere of the sintering treatment includes a reducing gas or a vacuum condition; wherein the reducing gas is hydrogen, or a mixed gas consisting of hydrogen and at least one of nitrogen and argon;
[0049] In an optional embodiment, the sintering temperature of the sintering treatment is 850°C to 1050°C;
[0050] In an optional embodiment, the holding time of the sintering treatment is 30 minutes to 180 minutes.
[0051] In an optional embodiment, after the rare earth mixture is sintered to obtain the tellurium-copper alloy material, the method further includes:
[0052] Performing a first cold rolling process on the tellurium-copper alloy material to obtain a deformed material;
[0053] performing a solution treatment, an aging treatment and a first pickling treatment on the deformed material to obtain a primary tellurium copper material;
[0054] In an optional embodiment, the first cold rolling process is orthogonal cyclic cold rolling;
[0055] In an optional embodiment, the first cold rolling process is performed 4 to 8 times; wherein the deformation amount of a single cold rolling process is 15% to 20%;
[0056] In an optional embodiment, the solution temperature of the solution treatment is 750°C to 850°C;
[0057] In an optional embodiment, the holding time of the solution treatment is 10 minutes to 60 minutes;
[0058] In an optional embodiment, after the solution treatment, the material is quenched;
[0059] In an optional embodiment, the temperature of the aging treatment is 250°C to 350°C;
[0060] In an optional embodiment, the holding time of the aging treatment is 60 minutes to 180 minutes;
[0061] In an optional embodiment, the pickling solution of the first pickling treatment is a dilute nitric acid aqueous solution;
[0062] In an optional embodiment, the dilute nitric acid aqueous solution is a 10% to 20% dilute nitric acid aqueous solution;
[0063] In an optional embodiment, the first pickling treatment lasts for 20 seconds to 60 seconds.
[0064] In an optional embodiment, after the deformed material is subjected to solution treatment, aging treatment and first pickling treatment to obtain a primary tellurium copper material, the method further includes:
[0065] The primary tellurium copper material is subjected to a second cold rolling treatment, an annealing treatment and a second pickling treatment to obtain a secondary tellurium copper material;
[0066] In an optional embodiment, the second cold rolling process is performed 4 to 8 times; wherein the deformation amount of a single cold rolling process is 5% to 10%;
[0067] In an optional embodiment, the annealing treatment temperature is 200° C. to 300° C.;
[0068] In an optional embodiment, the holding time of the annealing treatment is 5 minutes to 30 minutes;
[0069] In an optional embodiment, the pickling solution of the second pickling treatment is a dilute nitric acid aqueous solution;
[0070] In an optional embodiment, the dilute nitric acid aqueous solution is a 10% to 20% dilute nitric acid aqueous solution;
[0071] In an optional embodiment, the second pickling treatment lasts for 20 seconds to 60 seconds.
[0072] In a second aspect, the present invention provides a tellurium-copper alloy material prepared by the method for preparing the tellurium-copper alloy material as described in any one of the aforementioned embodiments.
[0073] Compared with the prior art, the present invention has the following beneficial effects:
[0074] The preparation method provided by the present invention can effectively improve the uniformity of the material and refine the grain structure by forming a tellurium copper complex solution and adopting a spray drying process during the preparation process of the tellurium copper alloy. The copper-based composite powder prepared by the spray drying method, the characterization of the microstructure and composition of the composite material, and the testing of the hardness, electrical conductivity, relative density and other properties show that the method can significantly affect the performance of the copper-based composite material. This uniform distribution helps to improve the electrical conductivity and tensile strength of the alloy, and also improves the high-temperature oxidation resistance and high-temperature gas corrosion resistance of the alloy.
[0075] The present invention evenly disperses nano-alumina particles in a tellurium-copper alloy by a solution spray drying method, achieving a significant dispersion strengthening effect, thereby improving the high-temperature strength of the material. The uniform distribution of the nano-dispersed phase effectively hinders dislocation movement and enhances grain boundary stability, thereby improving the yield strength and tensile strength of the alloy. In addition, the addition of nano-alumina particles also refines the grain size and enhances the heat resistance and oxidation resistance of the alloy. These characteristics enable the tellurium-copper alloy material to exhibit excellent performance in high-temperature application fields such as aerospace, automobiles, and electronics. This strengthening effect far exceeds traditional processes and provides a broader prospect for the application of alloy materials.
[0076] Doping with rare earth elements is an important step in the preparation of tellurium copper alloys, which has a significant impact on the properties of the alloy. The addition of rare earth elements can purify the alloy, refine the structure, and effectively hinder the growth of the alloy structure at high temperatures, thereby significantly improving the strength of the alloy. In addition, rare earth elements can also react with impurity elements in the alloy to form slag and be removed, thereby purifying the alloy, improving the purity of the alloy, and reducing the harmful effects of impurity elements on tellurium copper alloys.
[0077] Sintering is a key step in the preparation of tellurium copper alloys. The sintering temperature and time can be controlled to obtain a dense alloy material after sintering.
[0078] In addition, after the sintering treatment, other processing steps for optimizing the alloy material can be continued. For example, the material density can be further improved by material deformation treatment, such as cold rolling and / or hot rolling, and the microstructure of the material can be fibrous (similar to the internal fibers of bamboo). Moreover, this organizational structure can be further changed to an optimized structure by heat treatment, thereby optimizing the microstructure of the tellurium copper alloy and improving its performance.
[0079] In summary, the preparation method of tellurium copper alloy material can effectively improve the uniformity of the alloy, refine the grains, increase the strength and improve the thermoelectric performance by forming a tellurium copper complex solution, spray drying, doping with rare earth and precisely controlling the sintering process. These improvements not only enhance the physical properties of tellurium copper alloy, but also expand its potential in industrial applications. BRIEF DESCRIPTION OF THE DRAWINGS
[0080] In order to more clearly illustrate the specific implementation methods of the present invention or the technical solutions in the prior art, the drawings required for use in the specific implementation methods or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some implementation methods of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0081] Figure 1 Schematic diagram of the process of preparing the tellurium copper alloy material in the embodiment of the present application. DETAILED DESCRIPTION
[0082] The embodiments of the present invention will be described in detail below in conjunction with the examples, but it will be appreciated by those skilled in the art that the following examples are only used to illustrate the present invention and should not be considered as limiting the scope of the present invention. If no specific conditions are specified in the examples, the conditions are carried out according to normal conditions or the conditions recommended by the manufacturer. If the manufacturer of the reagents or instruments used is not specified, they are all conventional products that can be obtained commercially.
[0083] In an embodiment of the present application, a method for preparing a tellurium-copper alloy material is provided. The tellurium-copper alloy material is prepared by forming a tellurium-copper complex solution from a tellurium-copper raw material, subjecting the solution to a spray drying treatment, a calcination and a reduction treatment, and doping the solution with a rare earth raw material, followed by sintering.
[0084] The copper telluride raw material is a raw material for preparing the copper telluride alloy material in the present technology, which is formed into a copper telluride complex solution and then spray-dried, and may include copper ion-containing compounds, tellurium ion-containing compounds, and the like.
[0085] As mentioned above, the tellurium copper raw material is first subjected to the formation of a tellurium copper complex solution. By forming a tellurium copper complex solution, tellurium and copper can be more evenly mixed at the molecular level, which is crucial for subsequent spray drying, calcination and reduction processes. Uniform mixing helps to obtain alloy materials with uniform performance and improve the overall performance of the material. By forming a tellurium copper complex solution, the distribution of the second phase in the alloy can be improved, the segregation phenomenon at the grain boundary can be reduced, and the microstructure of the material can be optimized. This plays an important role in improving the electrical conductivity and mechanical properties of the alloy.
[0086] As mentioned above, spray drying is a process in which a liquid raw material is dispersed into extremely fine droplets through an atomizer and then brought into contact with a drying medium (usually hot air) to achieve rapid drying and obtain a solid product.
[0087] Spray drying plays a key role in the preparation of tellurium copper alloys. It atomizes the solution containing tellurium copper raw materials into fine droplets and contacts them with hot air to quickly evaporate the solvent, leaving a dry precursor powder with uniform element distribution. This uniformity is crucial for subsequent sintering and material properties. In addition, the powder particles prepared by spray drying are fine, with an average size of about 200 nanometers, which helps to improve the sintering characteristics of the powder, so that the relative density of the sintered alloy reaches more than 98%, close to full densification. The oxide composite powder after spray drying can form new alloy phases after reduction, such as Cu x Te, etc. These new phases form nano-scale grains with the original phases, improving the electrical conductivity and tensile strength of the material. At the same time, spray drying can also make the tellurium element, nano-ceramic phase and rare earth elements in the tellurium copper alloy highly uniformly distributed, improve the microstructure of the material, and improve its mechanical properties and thermal stability. Therefore, spray drying can not only prepare uniform and fine precursor powders, but also form a uniformly distributed alloy structure in the subsequent sintering and reduction process, significantly improving the comprehensive performance of the tellurium copper alloy.
[0088] By adopting the preparation method in this embodiment, the tellurium copper raw material and rare earth elements in the tellurium copper alloy are highly evenly distributed. This is due to the unique solution preparation, atomization drying and other process steps, which effectively avoid the common element segregation problem in the traditional smelting method, especially the more even distribution of elements at the grain boundaries, thereby significantly improving the overall performance of the material.
[0089] Since the uniformity of element distribution is significantly improved, the tellurium copper alloy prepared by the present technical solution exhibits stronger resistance to softening at high temperatures, which makes it possible for the alloy to serve under higher stress conditions and broadens its application range.
[0090] The uniformity of element distribution not only improves the mechanical strength of the alloy, but also maintains the excellent electrical conductivity of the tellurium copper alloy. The experimental results show that the electrical conductivity of the tellurium copper alloy material prepared by the method in this embodiment is about 5% to 10% higher than that of the traditional method, which is particularly important for applications in the fields of electronics and electrical engineering.
[0091] As mentioned above, through the calcination process, the precursor powder is heated in an air or oxygen atmosphere so that the metal elements therein are combined with oxygen to form a composite oxide. This step helps to remove organic matter and volatile substances in the powder, while promoting the formation of metal oxides, laying the foundation for the subsequent reduction process.
[0092] In the reduction treatment, the composite oxide is heated by introducing a reducing gas (such as hydrogen or a mixture of hydrogen, nitrogen and argon) to reduce the metal oxide to metal and form an Al2O3-CuTe alloy composite. This step is the key to achieving alloying, which ensures the uniform distribution of each element in the alloy, thereby improving the performance of the material.
[0093] As mentioned above, rare earth refers to the general term for 17 metal elements including lanthanide elements, scandium and yttrium in the periodic table. These 17 elements include lanthanum (La), cerium (Ce), praseodymium (Pr), neodymium (Nd), promethium (Pm), samarium (Sm), europium (Eu), gadolinium (Gd), terbium (Tb), dysprosium (Dy), holmium (Ho), erbium (Er), thulium (Tm), ytterbium (Yb), lutetium (Lu), and scandium (Sc) and yttrium (Y) closely related to lanthanide elements. The rare earth raw materials in the embodiments of the present application may include but are not limited to the above rare earth metal elements.
[0094] When preparing tellurium copper alloy, rare earth elements such as cerium-rich mixed rare earth are introduced mainly to refine the alloy grains and purify the grain boundaries. This refinement makes the fiber structure of the alloy denser, thereby improving the electrical conductivity and tensile strength. Grain refinement also helps to reduce the unevenness of deformation and reduce stress concentration, thereby reducing the risk of cracking. In addition, the addition of rare earth elements also significantly improves the oxidation resistance and gas corrosion resistance of tellurium copper alloy at high temperatures, especially in medium and high temperature environments, this oxidation resistance is particularly critical.
[0095] During the smelting process, rare earth elements react with impurity elements to form slag, which is removed, thereby purifying the alloy and improving its purity. This process not only reduces the harmful effects of impurity elements, but also improves the electrical conductivity of the alloy. When the content of mixed rare earth in rare earth tellurium copper alloy is controlled at 0.02% to 0.3%, the effect of grain refinement and grain boundary purification is most significant, making the alloy perform well in tensile strength, electrical conductivity and corrosion resistance, and has excellent comprehensive performance.
[0096] The addition of rare earth elements also enhances the corrosion resistance of the alloy, which is essential for extending the service life of the material and improving stability. At the same time, rare earth elements also significantly improve the strength of the alloy and effectively inhibit the excessive growth of the alloy structure at high temperatures. Therefore, tellurium copper alloys doped with rare earth elements play a positive role in grain refinement, improving electrical conductivity, enhancing high-temperature oxidation resistance, improving corrosion resistance, and improving mechanical properties, making them show more superior performance in many industrial applications.
[0097] In the process of preparing tellurium copper alloy materials, sintering treatment is a key step in the processing after doping with rare earth elements. Sintering not only promotes the interaction between rare earth elements and other elements in tellurium copper raw materials, but also helps to refine grains and purify grain boundaries, thereby enhancing the electrical conductivity and tensile strength of the alloy. In addition, sintering also helps to remove impurity elements, improve the purity of the alloy, and improve its oxidation resistance and corrosion resistance at high temperatures. By precisely controlling the temperature and time of sintering, the microstructure of the alloy can be optimized, ensuring the best effect of rare earth elements, so that tellurium copper alloys show excellent values in tensile strength, electrical conductivity, corrosion resistance and other aspects, and the comprehensive performance is more outstanding, suitable for a variety of industrial applications.
[0098] Specifically, the sintering temperature and time can be controlled to obtain a dense alloy material after sintering. After doping rare earth raw materials and briquetting, the obtained material can be a material with a porous structure and a non-dense material, and the relative density can reach 60% to 70%. The relative density of the material can be increased by sintering to reach more than 95%.
[0099] In some embodiments, reference Figure 1 , the preparation method of the tellurium copper alloy material comprises:
[0100] Step S1, using a metal chelating agent to prepare the copper telluride complex solution from the metal salt and telluric acid in the copper telluride raw material.
[0101] The copper telluride raw material includes a metal salt and telluric acid, wherein the metal salt can be a metal salt that can form a copper telluride complex with telluric acid, and can include a metal salt containing copper.
[0102] This step involves mixing the copper telluride raw materials (metal salts and telluric acid) with metal chelators to form a copper telluride complex solution. The role of the metal chelator is to form a stable complex with the metal ions and improve the dispersibility of the elements in the solution. The resulting copper telluride complex solution provides a uniform precursor for the subsequent spray drying process, which is conducive to the formation of a copper telluride alloy with uniform composition.
[0103] The use of metal chelators can improve the stability and uniformity of metal ions in the solution, reduce precipitation and aggregation, and help obtain a mixed solution with a more uniform distribution of elements.
[0104] Specifically, copper nitrate, telluric acid and aluminum nitrate can be mixed with the metal chelating agent in proportion according to stoichiometric calculation, and stirred sufficiently to form a uniform solution.
[0105] Step S2, spray drying the copper tellurium complex solution to obtain a precursor powder.
[0106] In the above step, the tellurium copper complex solution is converted into powder by spray drying technology. Spray drying is to atomize the solution into fine droplets, quickly evaporate the solvent by hot air, and leave dry powder. The precursor powder obtained in this step has a uniform chemical composition and a fine particle size, which is conducive to the subsequent sintering and alloying process.
[0107] As mentioned above, the powder particles prepared by the spray drying method are fine, which helps to improve the sintering characteristics of the powder, so that the relative density of the sintered alloy reaches more than 98%.
[0108] The morphology and particle size of the powder can be controlled by adjusting the spray drying parameters (such as air inlet temperature, atomizer speed, etc.).
[0109] Step S3, calcining and reducing the precursor powder to obtain an Al2O3-CuTe alloy composite.
[0110] As described above, the precursor powder is calcined to remove organic matter and nitrate ions, and then reduced to form an Al2O3-CuTe alloy composite. The Al2O3-CuTe alloy composite after calcination and reduction provides a uniformly distributed alloy precursor for subsequent sintering.
[0111] Calcination and reduction treatments help to form new alloy phases, such as Cu x Te, etc. These new phases and the original phases form nano-scale grains, thereby improving the electrical conductivity and tensile strength of the material.
[0112] The temperature, time and atmosphere of the calcination and reduction can be controlled to ensure complete conversion of the precursor powder to the desired alloy composite.
[0113] Step S4, mixing the Al2O3-CuTe alloy composite with a rare earth raw material to obtain a rare earth mixture.
[0114] As mentioned above, the Al2O3-CuTe alloy composite is mixed with a rare earth raw material to form a rare earth mixture. The rare earth mixture contains the Al2O3-CuTe alloy composite and rare earth elements, which provides a basis for preparing a high-performance tellurium copper alloy.
[0115] The addition of rare earth elements can purify the alloy, refine the structure, and effectively hinder the growth of the alloy structure at high temperature, thereby significantly improving the strength of the alloy.
[0116] Physical mixing or mechanical stirring can be used to ensure that the rare earth raw materials are evenly dispersed in the Al2O3-CuTe alloy composite.
[0117] Step S5, sintering the rare earth mixture to obtain the tellurium copper alloy material.
[0118] As mentioned above, the rare earth mixture is sintered to form a dense tellurium copper alloy material. The sintered tellurium copper alloy material has excellent mechanical and electrical properties. The sintering process helps the bonding and diffusion of particles, resulting in neck formation and densification, thereby obtaining complex mesh parts with excellent mechanical properties.
[0119] Specifically, the sintering temperature, atmosphere and pressure can be controlled to optimize the microstructure and properties of the tellurium copper alloy.
[0120] In this embodiment, the alumina dispersion-strengthened tellurium-copper alloy material containing rare earth metals prepared by the above method significantly improves the uniformity of element distribution, and the tellurium element, nano-ceramic phase (Al2O3) and rare earth elements in the tellurium-copper alloy material are highly uniformly distributed.
[0121] In the above steps of this embodiment, the synergistic effect is reflected in the calcination and reduction treatment and the addition of rare earth elements. The calcination and reduction treatment not only removes impurities in the precursor, but also promotes the formation of new alloy phases, such as CuTe xThe addition of rare earth elements and the mixing of Al2O3-CuTe alloy composites further improve the microstructure and properties of the alloy. These synergistic reactions work together to make the final tellurium copper alloy material have better comprehensive properties.
[0122] In some embodiments, the metal salt is a metal salt that is soluble in water and has no residual elements other than the target element after thermal decomposition.
[0123] The target element mentioned above is an element required to prepare the tellurium-copper alloy material and form a tellurium-copper complex solution, for example, copper.
[0124] In some embodiments, the metal salt includes a copper ion metal salt with copper as the target element.
[0125] In some embodiments, the metal salt further comprises an aluminum ion metal salt with aluminum as the target element.
[0126] In some embodiments, the copper ion metal salt includes copper nitrate and copper acetate.
[0127] In some embodiments, the aluminum ion metal salt includes aluminum nitrate and aluminum acetate.
[0128] The copper ion metal salts mentioned above may include but are not limited to copper nitrate and copper acetate, etc.; the aluminum ion metal salts may include but are not limited to aluminum nitrate and aluminum acetate, etc.; in addition, hydrates of these metal salts with crystal water may also be included, for example, copper nitrate trihydrate, aluminum nitrate nonahydrate, etc.
[0129] In some embodiments, the tellurium-copper alloy material includes 0.2-1.0 wt.% of tellurium, 0-0.5 wt.% of Al2O3, and 0-0.2 wt.% of the rare earth raw material.
[0130] In some embodiments, the step S1, using a metal chelating agent to prepare copper nitrate, aluminum nitrate and telluric acid to obtain the copper tellurium complex solution, comprises:
[0131] Step S11, dissolving the metal salt and telluric acid in water and mixing them into a solution.
[0132] The above steps involve dissolving solid raw materials such as metal salt and telluric acid in water to form a uniform solution.
[0133] For example, dissolving copper nitrate, aluminum nitrate, and telluric acid in water gives a solution containing copper, aluminum, and tellurium ions evenly distributed throughout the solution.
[0134] The water used may be conventional water, or may be deionized water, distilled water, double distilled water, ultrapure water, etc. For example, deionized water may be used to reduce impurities in the solution and avoid interference with subsequent reactions.
[0135] The above steps can be performed by stirring or heating (if necessary) to accelerate the dissolution process and ensure that all solid raw materials are completely dissolved.
[0136] Step S12, adding the metal chelating agent into the dissolving solution to form the tellurium copper complex solution containing the metal complex.
[0137] As mentioned above, a metal chelating agent, such as citric acid, is added to the already formed solution to react with the metal ions in the solution to form a stable metal complex, thereby obtaining a tellurium copper complex solution in which the metal ions are stably wrapped by the chelating agent to prevent aggregation and precipitation between the ions.
[0138] The use of chelating agents improves the stability of metal ions in the solution, helps maintain the uniformity of the solution, and provides a high-quality precursor solution for subsequent spray drying.
[0139] The amount of chelating agent added can be precisely controlled and adequate stirring can be used to ensure a uniform reaction.
[0140] In this embodiment, the coordination effect of the metal chelator and the metal ions improves the stability of the metal ions in the solution and reduces the aggregation and precipitation between the ions, which is crucial for the subsequent spray drying and sintering processes. The formation of the chelate helps to maintain the uniform distribution of the components in the solution, which is crucial for the uniformity and performance of the final alloy. The use of deionized water and chelating agents helps to reduce impurities in the solution, thereby reducing the impurity content in the final alloy and improving the purity and performance of the alloy.
[0141] Through the above two steps, a uniform and stable tellurium copper complex solution was prepared, which laid a good foundation for the subsequent spray drying and sintering treatment. This solution preparation method helps to improve the uniformity and performance of the final tellurium copper alloy material and reduce the performance differences caused by uneven distribution of raw materials.
[0142] In some embodiments, the metal chelator is required to meet the following two conditions at the same time:
[0143] (1) It contains hydroxyl functional groups that can form complexes with copper ions and aluminum ions.
[0144] (2) The material structure carries negative charges that can attach to the surface of the metal complex particles.
[0145] As mentioned above, the hydroxyl functional group (-OH) in the metal chelator can form a stable coordination bond with metal ions (such as copper ions Cu2+ and aluminum ions Al3+). This coordination is achieved through the interaction between the lone electron pair and the empty orbital of the metal ion, thereby forming a stable complex. This stability is crucial to maintaining the uniform distribution of metal ions in the solution because it prevents the metal ions from aggregating or precipitating in the solution, thereby ensuring the uniform distribution of each element in the tellurium copper alloy material and the consistency of the final performance during the subsequent spray drying and sintering process.
[0146] As mentioned above, the negative charge in the metal chelator molecule (such as the negative charge from the carboxyl group -COO-) helps to increase the surface negative charge of the particles in the solution. These negatively charged particles repel each other due to the same charges, which reduces the aggregation between particles and further increases the dispersibility. This repulsive effect helps to maintain the stability and uniformity of the metal complex in the solution and prevents the formation of large particles or aggregates during the preparation process, which is crucial for obtaining uniform tellurium copper alloy materials.
[0147] By meeting these two conditions, metal chelators can not only improve the stability of metal ions in the solution, but also reduce particle aggregation through charge repulsion, thereby achieving more uniform element distribution and better material properties during the preparation of tellurium copper alloys. This uniform distribution helps to improve the electrical conductivity, mechanical properties and high-temperature stability of the alloy, which is crucial for the application of tellurium copper alloys in industries such as electronics, electrical, automotive and aerospace.
[0148] In some embodiments, the metal chelator includes citric acid, ethylenediaminetetraacetic acid, nitrilotriacetic acid, and diethylenetriaminepentaacetic acid.
[0149] For example, the metal chelator can be citric acid (C6H8O7), the carboxyl group (-COOH) in its molecule has an active hydroxyl group that can react with metal ions such as Cu 2+ 、Al 3+ This complexation can prevent metal ions from aggregating and precipitating in the solution, thereby improving the dispersion of each element in the solution.
[0150] At the same time, citrate ions (C6H7O7-) are negatively charged. After forming complexes with metal ions, they increase the surface negative charge of particles in the solution. These negatively charged particles repel each other due to like charges, which reduces aggregation between particles and increases dispersibility.
[0151] In some embodiments, the step S2, spray drying the copper tellurium complex solution to obtain a precursor powder, comprises:
[0152] Step S21, atomizing the copper tellurium complex solution to form ultrafine droplets.
[0153] The above steps involve using an atomization device (such as a spray dryer) to disperse the tellurium copper complex solution into ultrafine droplets. Atomization is the process of converting a liquid into fine droplets, which helps to increase the surface area of the liquid in preparation for the subsequent drying process, thereby obtaining ultrafine droplets of the tellurium copper complex. The size and uniformity of these droplets have an important influence on the properties of the final powder.
[0154] Atomization treatment can make the copper telluride complex in the solution more evenly dispersed, laying the foundation for obtaining uniform powder.
[0155] Step S22, drying the ultrafine droplets by hot air to obtain the precursor powder.
[0156] In the above steps, hot air is used to dry the atomized ultrafine droplets to evaporate the solvent in the droplets, leaving dry powder, thereby obtaining precursor powder, which will be used for subsequent calcination and reduction treatment.
[0157] Hot air drying is a fast drying method that can obtain dry powder in a short time and helps to maintain the uniformity and chemical composition of the powder.
[0158] In this step, the droplets move along a spiral trajectory in the spray tower along with the high-temperature gas and are quickly dried to form a nearly spherical composite precursor powder, realizing the transformation from the tellurium copper complex solution to the precursor powder, and providing a basis for the subsequent heat treatment step.
[0159] The synergistic effect of atomization and hot air drying is that it can achieve uniform dispersion and rapid drying of tellurium copper complexes, which is essential for obtaining uniform precursor powders. The high-speed rotation of atomization and the high temperature of hot air drying can significantly improve drying efficiency and shorten production cycles. By precisely controlling the conditions of atomization and drying, the particle size and morphology of the powder can be adjusted, thereby affecting the properties of the final tellurium copper alloy material.
[0160] In some embodiments, the rotation speed of the atomization device for the atomization treatment is 4000 rpm to 30000 rpm. For example, the rotation speed may be 4000 rpm, 8000 rpm, 10000 rpm, 15000 rpm, 20000 rpm, 25000 rpm, 30000 rpm, and the like.
[0161] In some embodiments, the ultrafine droplets are dried by hot air, and the temperature of the air inlet is 100° C. to 300° C. For example, the temperature may be 100° C., 150° C., 200° C., 250° C., 300° C., and the like.
[0162] In some embodiments, the step S3, calcining and reducing the precursor powder to obtain an Al2O3-CuTe alloy composite, comprises:
[0163] Step S31, calcining the precursor powder in air or oxygen atmosphere to obtain a composite oxide.
[0164] In the above steps, the precursor powder is heated to a certain temperature in air or oxygen atmosphere to promote chemical reactions and physical changes to form composite oxides, and the obtained composite oxides are the basic materials for subsequent reduction treatment.
[0165] Calcination treatment helps to remove organic impurities and volatile substances in the precursor powder, while promoting the formation of metal oxides to prepare for the reduction reaction.
[0166] Step S32, introducing a reducing gas into the composite oxide for reduction treatment to obtain the Al2O3-CuTe alloy composite.
[0167] The above step involves exposing the composite oxide to a reducing gas to reduce the metal oxide to form an Al2O3-CuTe alloy composite. The Al2O3-CuTe alloy composite obtained is a raw material for subsequent sintering. In this step, a chemical reduction reaction is carried out and the metal oxide is reduced to a metal.
[0168] Reduction treatment helps to reduce metal oxides to metals and form alloy structures, which is crucial for improving the electrical conductivity and mechanical properties of the material.
[0169] In some embodiments, the calcination time of the calcination treatment is 10 minutes to 180 minutes. For example, the calcination time can be 10 minutes, 30 minutes, 50 minutes, 80 minutes, 100 minutes, 120 minutes, 150 minutes, 180 minutes, etc.
[0170] In some embodiments, the calcination temperature is 100°C to 600°C; for example, the temperature may be 100°C, 200°C, 300°C, 400°C, 500°C, 600°C, and the like.
[0171] In some embodiments, the temperature of the reduction treatment is 200°C to 800°C; for example, the temperature may be 200°C, 300°C, 400°C, 500°C, 600°C, 700°C, 800°C, and the like.
[0172] In some embodiments, the reduction time of the reduction treatment is 10 minutes to 180 minutes; for example, it can be 10 minutes, 30 minutes, 50 minutes, 80 minutes, 100 minutes, 150 minutes, 180 minutes, etc.
[0173] In some embodiments, the reducing gas for the reduction treatment includes any one of the following gases:
[0174] (1) Hydrogen;
[0175] (2) A mixture of hydrogen and nitrogen;
[0176] (3) A mixture of hydrogen and argon;
[0177] (4) A mixture of hydrogen, nitrogen and argon.
[0178] As mentioned above, in order to avoid introducing unnecessary impurities during the preparation process, various gases in the pure hydrogen or mixed gas used can be high-purity gases.
[0179] In some embodiments, the purity of the rare earth raw material is not less than 99%; and / or the particles of the rare earth raw material are less than 10 μm; and / or the treatment time of mixing the Al2O3-CuTe alloy composite with the rare earth raw material is 1 hour to 72 hours. For example, the treatment time can be 1 hour, 6 hours, 12 hours, 15 hours, 24 hours, 36 hours, 48 hours, 60 hours, 72 hours, etc.
[0180] As mentioned above, the rare earth powder and the Al2O3-CuTe alloy composite powder can be uniformly mixed in a variety of ways, such as a stirrer, a ball mill, a mixer, etc. These may include but are not limited to: a double-motion three-dimensional mixer, a rolling ball mill, a high-energy ball mill, a stirring ball mill, and a V-type mixer.
[0181] In some embodiments, the step S5 of sintering the rare earth mixture to obtain the tellurium-copper alloy material includes:
[0182] Step S51, forming the rare earth mixture to obtain a block.
[0183] Step S52: sintering the block to obtain the tellurium-copper alloy material.
[0184] As mentioned above, powder forming is an important step in the powder metallurgy process, which involves compressing metal or ceramic powder into the desired shape and size by physical means. The purpose of this process is to produce a powder body with a specific shape and size for subsequent sintering or other heat treatment processes. Its purpose is to produce a powder body with a specific shape for subsequent processing, as well as to increase the density and strength of the powder body so that it can withstand the pressure during handling and sintering.
[0185] In step S51, the rare earth mixture is formed into a block through a certain molding process to facilitate the subsequent sintering process. The obtained block is the preliminary shape of the sintering process and provides a physical basis for sintering. The molding process can ensure that the density and shape of the rare earth mixture meet the sintering requirements, which helps to improve the sintering efficiency and the performance of the final material.
[0186] As mentioned above, in step S52, the formed block is sintered in a specific atmosphere and temperature to form a dense tellurium-copper alloy material, so that the obtained tellurium-copper alloy material block has the required physical and chemical properties, such as high conductivity and good mechanical properties. The sintering process can significantly increase the density and strength of the material, reduce the porosity, and improve the overall performance of the material.
[0187] In some embodiments, the molding process includes any one of molding and cold isostatic pressing.
[0188] As mentioned above, pressing is a powder molding technology, usually carried out at room temperature. During the pressing process, powder is filled into a mold and then formed by applying external pressure. This pressure can be unidirectional, bidirectional or multidirectional, depending on the mold and the way the pressure is applied.
[0189] As mentioned above, Cold Isostatic Pressing (CIP) is a powder molding technology in which powder is isostatically pressed without heating. During the cold isostatic pressing process, the powder is placed in a flexible container (such as a rubber bag), and then the pressure is transmitted through a liquid medium (such as water or oil) so that the powder is evenly compressed in all directions.
[0190] In some embodiments, the pressure of the molding process is 50 MPa to 350 MPa. For example, the pressure may be 50 MPa, 80 MPa, 100 MPa, 150 MPa, 200 MPa, 250 MPa, 300 MPa, 350 MPa, etc.
[0191] In some embodiments, the holding time of the molding process is 5 seconds to 300 seconds. For example, the holding time can be 5 seconds, 10 seconds, 50 seconds, 100 seconds, 150 seconds, 200 seconds, 250 seconds, 300 seconds, etc.
[0192] In some embodiments, the sintering atmosphere of the sintering treatment includes a reducing gas or a vacuum condition; wherein the reducing gas is hydrogen, or a mixed gas consisting of hydrogen and at least one of nitrogen and argon. The reducing gas may be the same as or different from the gas in the aforementioned reduction treatment.
[0193] Specifically, the reducing gas for the reduction treatment includes any one of the following gases:
[0194] (1) Hydrogen;
[0195] (2) A mixture of hydrogen and nitrogen;
[0196] (3) A mixture of hydrogen and argon;
[0197] (4) A mixture of hydrogen, nitrogen and argon.
[0198] As mentioned above, in order to avoid introducing unnecessary impurities during the preparation process, various gases in the pure hydrogen or mixed gas used can be high-purity gases.
[0199] In some embodiments, the sintering temperature of the sintering process is 850°C to 1050°C;
[0200] In some embodiments, the holding time of the sintering treatment is 30 minutes to 180 minutes.
[0201] In some embodiments, after sintering the rare earth mixture to obtain the tellurium-copper alloy material, step S5 further includes:
[0202] Step S6, performing a first cold rolling process on the tellurium-copper alloy material to obtain a deformed material.
[0203] As mentioned above, the sintered tellurium-copper alloy material is cold-rolled to further refine the grain structure of the material and increase its density, thereby obtaining a tellurium-copper alloy material after cold rolling deformation, whose grains are more refined and the structure is more uniform.
[0204] Cold rolling can significantly improve the strength and hardness of the material while reducing the thickness and size of the material. Specifically, uniform deformation of the material can be achieved by controlling the number of cold rolling times and the amount of deformation in a single cold rolling and by using orthogonal cyclic cold rolling.
[0205] Step S7, performing solution treatment, aging treatment and first pickling treatment on the deformed material to obtain a primary tellurium copper material.
[0206] As mentioned above, solution treatment is a metal heat treatment process, the main purpose of which is to improve the plasticity and toughness of the alloy and prepare the structure for subsequent aging treatment. During the solution treatment process, the alloy is heated to an appropriate temperature and maintained for a long enough time so that the soluble phase is fully dissolved into the solid solution matrix, and then quickly cooled to room temperature to form a supersaturated solid solution. This treatment can improve the strength and corrosion resistance of the alloy, and help eliminate stress and soften it for further processing or forming.
[0207] As mentioned above, aging treatment is a metal heat treatment process, mainly applied to alloy workpieces, especially after solution treatment, cold plastic deformation or casting, forging. The purpose of this process is to change the properties, shape and size of the workpiece over time at a higher temperature or room temperature.
[0208] The first pickling treatment and the second pickling treatment in the subsequent step are both surface treatment methods for materials, and their purpose is to remove the surface oxides of the alloy material. The conditions and methods of the two pickling treatments can be the same or different.
[0209] As mentioned above, the deformed material after cold rolling is heated to a certain temperature, maintained for a certain period of time, and then quenched to achieve the formation of a solid solution. The result is a tellurium-copper alloy material that has undergone solid solution treatment, and the alloy elements inside it are more evenly distributed. Solid solution treatment helps to improve the corrosion resistance and mechanical properties of the material, while creating conditions for aging treatment.
[0210] The best solution treatment effect can be obtained by controlling the temperature and time of solution treatment and the cooling rate of quenching.
[0211] In some embodiments, the first cold rolling process is orthogonal cyclic cold rolling.
[0212] As mentioned above, orthogonal cyclic cold rolling is a special cold rolling process, which involves the process of alternating cold rolling deformation in two perpendicular directions.
[0213] In some embodiments, the first cold rolling process is performed 4 to 8 times; for example, the number of times may be 4, 5, 6, 7, 8, etc. The deformation amount of a single cold rolling process is 15% to 20%; for example, it may be 15%, 16%, 17%, 18%, 19%, 20%, etc.
[0214] In some embodiments, the solution temperature of the solution treatment is 750°C to 850°C; for example, the solution temperature may be 750°C, 780°C, 800°C, 820°C, 830°C, 850°C, and the like.
[0215] In some embodiments, the holding time of the solution treatment is 10 minutes to 60 minutes; for example, the holding time can be 10 minutes, 20 minutes, 30 minutes, 40 minutes, 50 minutes, 60 minutes, etc.
[0216] In some embodiments, after the solution treatment, the material is quenched.
[0217] As mentioned above, quenching is a step after solution treatment, the purpose of which is to "freeze" the solute atoms in the solid solution by rapid cooling to prevent the precipitation of the second phase, thereby obtaining the maximum supersaturation. This rapid cooling operation helps to obtain the highest strength and the best corrosion resistance. The quenching medium can be water, oil or other special organic media.
[0218] As mentioned above, the reasons for quenching after solution treatment mainly include improving the strength and hardness of the material, which is crucial for many engineering applications; rapid cooling can inhibit the re-precipitation of the second phase dissolved during solution treatment and maintain the supersaturated solid solution state, which is very necessary for obtaining certain special physical and chemical properties; for some alloys, such as stainless steel, quenching can also improve its corrosion resistance; in addition, quenching treatment prepares for subsequent aging treatment, allowing the supersaturated solid solution to be precipitated during aging treatment, thereby further enhancing the hardness and strength of the alloy.
[0219] In some embodiments, the temperature of the aging treatment is 250° C. to 350° C. For example, the temperature may be 250° C., 280° C., 300° C., 350° C., and the like.
[0220] In some embodiments, the holding time of the aging treatment is 60 minutes to 180 minutes; for example, the holding time can be 60 minutes, 80 minutes, 100 minutes, 120 minutes, 150 minutes, 180 minutes, etc.
[0221] In some embodiments, the pickling solution of the first pickling treatment is a dilute nitric acid aqueous solution;
[0222] In some embodiments, the dilute nitric acid aqueous solution is a 10% to 20% dilute nitric acid aqueous solution; for example, the concentration of the dilute nitric acid aqueous solution may be 10%, 15%, 20%, and the like.
[0223] In some embodiments, the first pickling treatment lasts for 20 seconds to 60 seconds, for example, 20 seconds, 30 seconds, 40 seconds, 50 seconds, 60 seconds, etc.
[0224] In some embodiments, the step S7, after performing a solution treatment, an aging treatment and a first pickling treatment on the deformed material to obtain a primary tellurium copper material, further comprises:
[0225] Step S8, performing a second cold rolling treatment, an annealing treatment and a second pickling treatment on the primary tellurium copper material to obtain a secondary tellurium copper material.
[0226] In some embodiments, the second cold rolling process is performed 4 to 8 times; for example, the number of times may be 4, 5, 6, 7, 8, etc. The deformation amount of a single cold rolling process is 5% to 10%; for example, it may be 5%, 6%, 7%, 8%, 9%, 10%, etc.
[0227] In some embodiments, the annealing temperature is 200°C to 300°C; for example, the annealing temperature can be 200°C, 220°C, 250°C, 280°C, 300°C, etc.
[0228] In some embodiments, the holding time of the annealing treatment is 5 minutes to 30 minutes; for example, the holding time of the annealing treatment can be 5 minutes, 8 minutes, 10 minutes, 15 minutes, 20 minutes, 25 minutes, 30 minutes, etc.
[0229] In some embodiments, the pickling solution of the second pickling treatment is a dilute nitric acid aqueous solution;
[0230] In some embodiments, the dilute nitric acid aqueous solution is a 10% to 20% dilute nitric acid aqueous solution; for example, the concentration of the dilute nitric acid aqueous solution may be 10%, 15%, 20%, and the like.
[0231] In some embodiments, the second pickling treatment lasts for 20 seconds to 60 seconds, for example, 20 seconds, 30 seconds, 40 seconds, 50 seconds, 60 seconds, etc.
[0232] In an embodiment of the present application, a tellurium-copper alloy material is provided, which is prepared by the method for preparing the tellurium-copper alloy material as described in any one of the aforementioned embodiments.
[0233] Example 1
[0234] In this embodiment, the tellurium copper alloy material was prepared by the following method.
[0235] Experimental methods:
[0236] (1) 18802 g of copper nitrate trihydrate, 36 g of telluric acid, 55 g of aluminum nitrate nonahydrate and 1000 g of citric acid were added to 30 kg of deionized water at 90° C. and stirred for 60 minutes;
[0237] (2) atomizing the solution into ultrafine droplets in a spray drying tower and rapidly drying the solution with hot air, wherein the atomizing disk speed is set to 18000 rpm, the feed rate is set to 5 kg / h, and the air inlet temperature is set to 180° C. to obtain a precursor powder;
[0238] (3) placing the precursor powder in a corundum boat with a layer thickness of about 5 mm, calcining at a temperature of 350° C. for 60 minutes to obtain a composite oxide;
[0239] (4) placing the composite oxide powder in a corundum boat and reducing it in a tube furnace, wherein the material layer thickness is about 5 mm, the reducing atmosphere is 75% hydrogen + 25% nitrogen, the gas purity is greater than 99.99%, the reduction temperature is 400° C., and the holding time is 90 minutes to obtain an Al2O3-CuTe alloy composite;
[0240] (5) 0.9 g of yttrium powder and 3000 g of Al2O3-CuTe alloy composite were placed in a double-motion three-dimensional mixer for mixing at a barrel speed of 20 rpm, a blade speed of 60 rpm, and a mixing time of 24 h to obtain a rare earth mixture;
[0241] (6) forming the Y-Al2O3-CuTe alloy composite powder (rare earth mixture) into a block by cold isostatic pressing, the forming pressure is 180 MPa, the holding time is 90 s, and a block is obtained;
[0242] (7) placing the block in a hydrogen furnace for sintering at a sintering temperature of 930° C. for a holding time of 60 min to obtain a sintered tellurium copper alloy material;
[0243] (8) First cold rolling treatment: the sintered blank (the tellurium-copper alloy material after sintering) is subjected to orthogonal cyclic cold rolling for 6 times, with a single deformation amount of 20%, to obtain a deformed material;
[0244] (9) The deformed material is subjected to solution treatment at a temperature of 800°C for a holding time of 20 min, and then the blank is quenched in water;
[0245] (10) subjecting the deformed material after quenching to aging treatment, the aging temperature is 280°C, and the holding time is 90 min;
[0246] (11) First pickling treatment: the deformed material after aging treatment is pickled in a 15% dilute nitric acid aqueous solution for 40 seconds to obtain a primary tellurium copper material;
[0247] (12) Second cold rolling treatment: the tellurium copper material is subjected to unidirectional cold rolling for 6 times, and the deformation of each cold rolling is 8%;
[0248] (13) The primary tellurium copper material after the second cold rolling treatment is annealed at a temperature of 230° C. for a holding time of 10 min to obtain a secondary tellurium copper material, namely, an alumina dispersion-strengthened tellurium copper alloy material containing rare earth metals.
[0249] The tellurium-copper alloy material prepared in this embodiment has the following alloy components: Te: 0.40wt.%, Al2O3: 0.15wt.%, Y: 0.03wt.%, and the balance is Cu.
[0250] The tellurium copper alloy material has a tensile strength of 455MPa, an electrical conductivity of 92%IACS, a thermal conductivity of 362W / (m·K), an elongation of 11%, a hardness of 60HRB, and a softening temperature of 810°C. It has good mechanical properties, electrical and thermal conductivity, and a high softening temperature.
[0251] Example 2
[0252] In this embodiment, the tellurium copper alloy material was prepared by the following method.
[0253] Experimental methods:
[0254] (1) 22560 g of copper nitrate trihydrate, 43 g of telluric acid, 66 g of aluminum nitrate nonahydrate and 1200 g of citric acid were added to 40 kg of deionized water at a water temperature of 80° C. and stirred for 120 minutes;
[0255] (2) atomizing the solution into ultrafine droplets in a spray drying tower and rapidly drying the solution with hot air, wherein the atomizing disk speed is set to 22000 rpm, the feed rate is set to 6 kg / h, and the air inlet temperature is set to 150° C. to obtain a precursor powder;
[0256] (3) placing the precursor powder in a corundum boat with a layer thickness of about 6 mm, calcining at 400° C. for 40 minutes to obtain a composite oxide;
[0257] (4) placing the composite oxide powder in a corundum boat and reducing it in a tube furnace, wherein the material layer thickness is about 6 mm, the reducing atmosphere is hydrogen, the gas purity is greater than 99.99%, the reduction temperature is 500° C., and the holding time is 60 minutes to obtain an Al2O3-CuTe alloy composite;
[0258] (5) 2.4 g of lanthanum powder and 3000 g of Al2O3-CuTe alloy composite powder were placed in a double-motion three-dimensional mixer for mixing at a barrel speed of 25 rpm, a blade speed of 70 rpm, and a mixing time of 36 h to obtain a rare earth mixture;
[0259] (6) forming the La-Al2O3-CuTe alloy composite powder into a block by cold isostatic pressing, the forming pressure is 200 MPa, the holding time is 70 s, and a block is obtained;
[0260] (7) placing the tellurium-copper alloy block in a hydrogen furnace for sintering at a sintering temperature of 1000° C. for a holding time of 90 min to obtain a sintered tellurium-copper alloy material;
[0261] (8) First cold rolling treatment: the sintered billet is subjected to 8 cycles of orthogonal cold rolling, with a single deformation amount of 15%, to obtain a deformed material;
[0262] (9) The deformed material is subjected to solution treatment at a temperature of 850°C for a holding time of 15 min, and then the blank is quenched in water;
[0263] (10) subjecting the deformed material after quenching to aging treatment, the aging temperature is 250° C., and the holding time is 120 min;
[0264] (11) First pickling treatment: the deformed material after aging treatment is pickled in a 20% dilute nitric acid aqueous solution for 20 seconds to obtain a primary tellurium copper material;
[0265] (12) Second cold rolling treatment: the tellurium copper material is subjected to unidirectional cold rolling 8 times, and the deformation of each cold rolling is 6%;
[0266] (13) The primary tellurium copper material after the second cold rolling treatment is annealed at a temperature of 250° C. for a holding time of 15 min to obtain a secondary tellurium copper material, namely, an alumina dispersion-strengthened tellurium copper alloy material containing rare earth metals.
[0267] The alloy composition of the tellurium copper alloy material prepared in this embodiment is: Te: 0.40wt.%, Al2O3: 0.15wt.%, La: 0.08wt.%, and the balance is Cu. The tellurium copper alloy material has a tensile strength of 486MPa, a conductivity of 96%IACS, a thermal conductivity of 380W / (m·K), an elongation of 19%, a hardness of 63HRB, and a softening temperature of 860°C, and has good mechanical properties, electrical conductivity, thermal conductivity, and a high softening temperature.
[0268] Example 3
[0269] In this embodiment, the tellurium copper alloy material was prepared by the following method.
[0270] Experimental methods:
[0271] (1) 18762 g of copper nitrate trihydrate, 45 g of telluric acid, 92 g of aluminum nitrate nonahydrate and 1300 g of citric acid were added to 35 kg of deionized water at a water temperature of 85° C. and stirred for 90 minutes;
[0272] (2) atomizing the solution into ultrafine droplets in a spray drying tower and rapidly drying the solution with hot air, wherein the atomizing disk speed is set to 13000 rpm, the feed rate is set to 3 kg / h, and the air inlet temperature is set to 130° C. to obtain a precursor powder;
[0273] (3) placing the precursor powder in a corundum boat with a layer thickness of about 10 mm, calcining at 450° C. for 30 minutes to obtain a composite oxide;
[0274] (4) placing the composite oxide powder in a corundum boat and reducing it in a tube furnace, wherein the material layer thickness is about 10 mm, the reducing atmosphere is 70% hydrogen + 30% argon, the gas purity is greater than 99.99%, the reducing temperature is 600° C., and the holding time is 40 minutes to obtain an Al2O3-CuTe alloy composite;
[0275] (5) 1.5 g of cerium powder and 3000 g of Al2O3-CuTe alloy composite powder were placed in a rolling ball mill for mixing. In order to avoid the introduction of non-volatile impurities due to friction, a polyurethane ball mill was used, pure copper grinding balls were used, the ball-to-material ratio was 5:1, and the ball milling time was 48 h to obtain a rare earth mixture;
[0276] (6) forming the Ce-Al2O3-CuTe alloy composite powder into a block by cold isostatic pressing, the molding pressure is 150 MPa, and the holding time is 120 s to obtain a block;
[0277] (7) placing the tellurium-copper alloy block in a hydrogen furnace for sintering at a sintering temperature of 1050° C. for a holding time of 80 min to obtain a sintered tellurium-copper alloy material;
[0278] (8) First cold rolling treatment: the sintered billet is subjected to orthogonal cold rolling for 5 times, with a single deformation amount of 18% to obtain a deformed material;
[0279] (9) The deformed material is subjected to solution treatment at a temperature of 760°C for 40 min, and then the blank is quenched in water;
[0280] (10) The deformed material after quenching treatment is subjected to aging treatment, the aging temperature is 320°C, and the holding time is 60 min;
[0281] (11) First pickling treatment: the deformed material after aging treatment is pickled in a 20% dilute nitric acid aqueous solution for 15 seconds to obtain a primary tellurium copper material;
[0282] (12) Second cold rolling treatment: the tellurium copper material is subjected to unidirectional cold rolling for 5 times, and the deformation of each cold rolling is 10%;
[0283] (13) The tellurium copper material after the second cold rolling treatment is annealed at a temperature of 280° C. and a holding time of 10 min.
[0284] The alloy composition of the tellurium copper alloy material prepared in this embodiment is: Te: 0.50wt.%, Al2O3: 0.25wt.%, Ce: 0.05wt.%, and the balance is Cu. The tellurium copper alloy material has a tensile strength of 518MPa, a conductivity of 92%IACS, a thermal conductivity of 361W / (m·K), an elongation of 13%, a hardness of 68HRB, and a softening temperature of 895°C, and has good mechanical properties, electrical conductivity, thermal conductivity, and a high softening temperature.
[0285] Example 4
[0286] In this embodiment, the tellurium copper alloy material was prepared by the following method.
[0287] Experimental methods:
[0288] (1) 22514 g of copper nitrate trihydrate, 54 g of telluric acid, 110 g of aluminum nitrate nonahydrate and 1500 g of citric acid were added to 35 kg of deionized water at 90° C. and stirred for 120 minutes;
[0289] (2) atomizing the solution into ultrafine droplets in a spray drying tower and rapidly drying the solution with hot air, wherein the atomizing disk speed is set to 26000 rpm, the feed rate is set to 8 kg / h, and the air inlet temperature is set to 200° C. to obtain a precursor powder;
[0290] (3) placing the precursor powder in a corundum boat with a layer thickness of about 5 mm, calcining at 400° C. for 120 minutes to obtain a composite oxide;
[0291] (4) placing the composite oxide powder in a corundum boat and reducing it in a tube furnace, wherein the material layer thickness is about 5 mm, the reducing atmosphere is hydrogen, the gas purity is greater than 99.99%, the reduction temperature is 700° C., the holding time is 30 minutes, and the composite oxide is obtained to obtain an Al2O3-CuTe alloy composite;
[0292] (5) 3.2 g of lanthanum powder and 4000 g of Al2O3-CuTe alloy composite powder were placed in a V-type mixer and mixed at a speed of 45 rpm for 24 h to obtain a rare earth mixture;
[0293] (6) forming the La-Al2O3-CuTe alloy composite powder into a block by using a hydraulic press, the forming pressure is 300 MPa, the holding time is 10 s, and a block is obtained;
[0294] (7) placing the tellurium copper alloy block in a hydrogen furnace for sintering at a sintering temperature of 850° C. and a holding time of 120 min to obtain a deformed material;
[0295] (8) The sintered billet is subjected to orthogonal cyclic cold rolling for 4 times, with a single deformation of 20%;
[0296] (9) The deformed material is subjected to solution treatment at a temperature of 750°C for a holding time of 60 min, and then the blank is quenched in water;
[0297] (10) subjecting the deformed material after quenching to aging treatment, the aging temperature is 300° C., and the holding time is 120 min;
[0298] (11) pickling the deformed material after aging treatment in a 15% dilute nitric acid aqueous solution for 30 seconds to obtain a primary tellurium copper material;
[0299] (12) the tellurium-copper alloy block after S11 is subjected to unidirectional cold rolling for 8 times, and the deformation of each cold rolling is 5%;
[0300] (13) The primary tellurium copper material after the second cold rolling treatment is annealed at a temperature of 200° C. and a holding time of 25 min to obtain a secondary tellurium copper material, namely, an alumina dispersion-strengthened tellurium copper alloy material containing rare earth metals.
[0301] The alloy composition of the tellurium copper alloy material prepared in this embodiment is: Te: 0.50wt.%, Al2O3: 0.25wt.%, La: 0.08wt.%, and the balance is Cu. The tellurium copper alloy material has a tensile strength of 515MPa, a conductivity of 94%IACS, a thermal conductivity of 375W / (m·K), an elongation of 16%, a hardness of 67HRB, and a softening temperature of 900°C, and has good mechanical properties, electrical conductivity, thermal conductivity, and a high softening temperature.
[0302] Example 5
[0303] In this embodiment, the tellurium copper alloy material was prepared by the following method.
[0304] Experimental methods:
[0305] (1) 18781 g of copper nitrate trihydrate, 27 g of telluric acid, 129 g of aluminum nitrate nonahydrate and 1000 g of citric acid were added to 40 kg of deionized water at 90° C. and stirred for 90 minutes;
[0306] (2) atomizing the solution into ultrafine droplets in a spray drying tower and rapidly drying the solution with hot air, wherein the atomizing disk speed is set to 15000 rpm, the feed rate is set to 5 kg / h, and the air inlet temperature is set to 170° C. to obtain a precursor powder;
[0307] (3) placing the precursor powder in a corundum boat with a layer thickness of about 6 mm, calcining at a temperature of 450° C. for 90 minutes to obtain a composite oxide;
[0308] (4) placing the composite oxide powder in a corundum boat and reducing it in a tube furnace, wherein the material layer thickness is about 6 mm, the reducing atmosphere is 70% hydrogen + 30% nitrogen, the gas purity is greater than 99.99%, the reduction temperature is 500° C., and the holding time is 120 minutes to obtain an Al2O3-CuTe alloy composite;
[0309] (5) 2.0 g of lanthanum powder and 4000 g of Al2O3-CuTe alloy composite powder were mixed in a double-motion three-dimensional mixer at a barrel speed of 20 rpm, a blade speed of 80 rpm, and a mixing time of 12 h to obtain a rare earth mixture;
[0310] (6) forming the La-Al2O3-CuTe alloy composite powder into a block by using a hydraulic press, the forming pressure is 350 MPa, the holding time is 10 s, and a block is obtained;
[0311] (7) placing the tellurium-copper alloy block in a hydrogen furnace for sintering at a sintering temperature of 900° C. for a holding time of 150 min to obtain a sintered tellurium-copper alloy material;
[0312] (8) First cold rolling treatment: the sintered billet is subjected to 8 cycles of orthogonal cold rolling, with a single deformation amount of 8%, to obtain a deformed material;
[0313] (9) The deformed material is subjected to solution treatment at a temperature of 800°C for a holding time of 20 min, and then the blank is quenched in water;
[0314] (10) subjecting the deformed material after quenching to aging treatment, with an aging temperature of 280° C. and a holding time of 180 min;
[0315] (11) First pickling treatment: the deformed material after aging treatment is pickled in a 15% dilute nitric acid aqueous solution for 30 seconds to obtain a primary tellurium copper material;
[0316] (12) Second cold rolling treatment: the tellurium copper alloy block after S11 is subjected to unidirectional cold rolling for 6 times, and the deformation of each cold rolling is 8%;
[0317] (13) The primary tellurium copper material after the second cold rolling treatment is annealed at a temperature of 280° C. for a holding time of 20 min to obtain a secondary tellurium copper material, namely, an alumina dispersion-strengthened tellurium copper alloy material containing rare earth metals.
[0318] The alloy composition of the tellurium copper alloy material prepared in this embodiment is: Te: 0.30wt.%, Al2O3: 0.35wt.%, La: 0.05wt.%, and the balance is Cu. The tellurium copper alloy material has a tensile strength of 575MPa, a conductivity of 90%IACS, a thermal conductivity of 351W / (m·K), an elongation of 10%, a hardness of 73HRB, and a softening temperature of 930°C, and has good mechanical properties, electrical conductivity, thermal conductivity, and a high softening temperature.
[0319] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein by equivalents. However, these modifications or replacements do not make the essence of the corresponding technical solutions deviate from the scope of the technical solutions of the embodiments of the present invention.
Claims
1. A method for preparing a tellurium copper alloy material, characterized in that: The tellurium-copper alloy material is prepared by forming a tellurium-copper complex solution from a tellurium-copper raw material, spray drying, calcining and reducing the solution, doping the solution with a rare earth raw material, and sintering the solution.
2. The method for preparing the tellurium-copper alloy material according to claim 1, characterized in that: include: The copper telluride complex solution is prepared by using a metal chelating agent to prepare the metal salt and telluric acid in the copper telluride raw material; spray drying the copper tellurium complex solution to obtain a precursor powder; The precursor powder is subjected to calcination and reduction treatment to obtain an Al2O3-CuTe alloy composite; Mixing the Al2O3-CuTe alloy composite with a rare earth raw material to obtain a rare earth mixture; The rare earth mixture is sintered to obtain the tellurium-copper alloy material; Preferably, the metal salt is a metal salt that is soluble in water and has no residual elements other than the target element after thermal decomposition; Preferably, the metal salt comprises a copper ion metal salt with copper as the target element; Preferably, the metal salt further comprises an aluminum ion metal salt with aluminum as the target element; Preferably, the copper ion metal salt includes copper nitrate and copper acetate; Preferably, the aluminum ion metal salt includes aluminum nitrate and aluminum acetate; Preferably, the tellurium-copper alloy material comprises 0.2-1.0 wt.% of tellurium, 0-0.5 wt.% of Al2O3, and 0-0.2 wt.% of the rare earth raw material.
3. The method for preparing the tellurium-copper alloy material according to claim 2, characterized in that: The method of using a metal chelating agent to prepare the copper telluride complex solution from the metal salt and telluric acid in the copper telluride raw material comprises: Dissolving the metal salt and telluric acid in water and mixing them into a solution; adding the metal chelating agent to the dissolving solution to form the tellurium copper complex solution containing the metal complex; Preferably, the metal chelating agent contains a hydroxyl functional group capable of forming a complex with copper ions and aluminum ions; and the material structure of the metal chelating agent carries a negative charge capable of attaching to the surface of the metal complex particles; Preferably, the metal chelating agent comprises citric acid, ethylenediaminetetraacetic acid, nitrilotriacetic acid and diethylenetriaminepentaacetic acid.
4. The method for preparing the tellurium-copper alloy material according to claim 2, characterized in that: The step of spray drying the copper tellurium complex solution to obtain a precursor powder comprises: atomizing the copper tellurium complex solution to form ultrafine droplets; Drying the ultrafine droplets by hot air to obtain the precursor powder; Preferably, the rotation speed of the atomization equipment for the atomization treatment is 4000rpm to 30000rpm; Preferably, the ultrafine droplets are dried by hot air, and the temperature of the air inlet is 100°C to 300°C.
5. The method for preparing the tellurium-copper alloy material according to claim 2, characterized in that: The precursor powder is subjected to calcination and reduction treatment to obtain an Al2O3-CuTe alloy composite, comprising: calcining the precursor powder in air or oxygen atmosphere to obtain a composite oxide; Passing a reducing gas into the composite oxide for reduction treatment to obtain the Al2O3-CuTe alloy composite; Preferably, the calcination time of the calcination treatment is 10 minutes to 180 minutes; Preferably, the calcination temperature is 100°C to 600°C; Preferably, the temperature of the reduction treatment is 200°C to 800°C; Preferably, the reduction time of the reduction treatment is 10 minutes to 180 minutes; Preferably, the reducing gas for the reduction treatment includes hydrogen, or a mixed gas consisting of hydrogen and at least one of nitrogen and argon.
6. The method for preparing the tellurium-copper alloy material according to claim 2, characterized in that: The purity of the rare earth raw material is not less than 99%; and / or, The particles of the rare earth raw material are smaller than 10 μm; and / or, The treatment time of mixing the Al2O3-CuTe alloy composite with the rare earth raw material is 1 hour to 72 hours.
7. The method for preparing the tellurium-copper alloy material according to claim 2, characterized in that: The process of sintering the rare earth mixture to obtain the tellurium-copper alloy material comprises: Performing a molding process on the rare earth mixture to obtain a block; sintering the block to obtain the tellurium-copper alloy material; Preferably, the molding process comprises any one of molding and cold isostatic pressing; Preferably, the pressure of the molding process is 50MPa to 350MPa; Preferably, the holding time of the molding process is 5 seconds to 300 seconds; Preferably, the sintering atmosphere of the sintering treatment includes a reducing gas or a vacuum condition; wherein the reducing gas is hydrogen, or a mixed gas consisting of hydrogen and at least one of nitrogen and argon; Preferably, the sintering temperature of the sintering treatment is 850°C to 1050°C; Preferably, the holding time of the sintering treatment is 30 minutes to 180 minutes.
8. The method for preparing the tellurium-copper alloy material according to claim 2, characterized in that: After the rare earth mixture is sintered to obtain the tellurium-copper alloy material, the method further includes: Performing a first cold rolling process on the tellurium-copper alloy material to obtain a deformed material; performing a solution treatment, an aging treatment and a first pickling treatment on the deformed material to obtain a primary tellurium copper material; Preferably, the first cold rolling process is orthogonal cyclic cold rolling; Preferably, the first cold rolling process is performed 4 to 8 times; wherein the deformation amount of a single cold rolling process is 15% to 20%; Preferably, the solution temperature of the solution treatment is 750°C to 850°C; Preferably, the holding time of the solution treatment is 10 minutes to 60 minutes; Preferably, after the solution treatment, the material is quenched; Preferably, the temperature of the aging treatment is 250°C to 350°C; Preferably, the holding time of the aging treatment is 60 minutes to 180 minutes; Preferably, the pickling solution of the first pickling treatment is a dilute nitric acid aqueous solution; Preferably, the dilute nitric acid aqueous solution is a 10% to 20% dilute nitric acid aqueous solution; Preferably, the first pickling treatment lasts for 20 seconds to 60 seconds.
9. The method for preparing the tellurium-copper alloy material according to claim 8, characterized in that: After the deformed material is subjected to solution treatment, aging treatment and first pickling treatment to obtain a primary tellurium copper material, the method further includes: The primary tellurium copper material is subjected to a second cold rolling treatment, an annealing treatment and a second pickling treatment to obtain a secondary tellurium copper material; Preferably, the second cold rolling process is performed 4 to 8 times; wherein the deformation amount of a single cold rolling process is 5% to 10%; Preferably, the annealing temperature is 200°C to 300°C; Preferably, the holding time of the annealing treatment is 5 minutes to 30 minutes; Preferably, the pickling solution of the second pickling treatment is a dilute nitric acid aqueous solution; Preferably, the dilute nitric acid aqueous solution is a 10% to 20% dilute nitric acid aqueous solution; Preferably, the second pickling treatment lasts for 20 seconds to 60 seconds.
10. A tellurium copper alloy material, characterized in that: The tellurium-copper alloy material is prepared by the method for preparing the tellurium-copper alloy material as described in any one of claims 1 to 9.
Citation Information
Patent Citations
Method for preparing nano tungsten-copper-rare earth composite powder
CN101875134A
Method for extracting semiconductor elements through photoelectrochemistry metallurgy
CN105088262A
Preparation method for tellurium-copper alloy material
CN110284024A
Method for synchronously separating and extracting scattered element tellurium and metal copper from cuprous telluride slag
CN113337724A
Method for efficiently recovering scattered metal tellurium from cuprous telluride slag
CN113373314A